Ukraine : Moving Forward on Regional Development and Regional Policy - World Bank (Washington, DC, 2013)
The report considers the evolving experience in Ukraine, and looks at lessons from other countries in order to spur thinking about how best to move forward in the development of regional policy. In the context of a transition economy, accurately measuring the changes that are underway is difficult. The statistical system itself is in transition, and there are a wide range of activities that go unrecorded. Official statistics suggest that disparities among the regions have increased since the mid-1990s in Ukraine, and data also suggest that many of the regions in the west that focus on heavy industry, plus Kyiv, continue to have the strongest economic performance. In contrast, regions in the far west of the country have the lowest per capita gross value added (GVA). On reviewing regional development policy, some of the factors that may explain the lack of effectiveness are as follows: weak framework in setting objectives and priorities; no fiscal parameters; ad hoc allocation of investment; reliance on heavy state intervention; and, top-down versus bottom-up. In order to build a long-term base for regional development, and improve the effectiveness of policy in the short term, there are a number of steps to be taken as follows: there is need to clarify who is responsible for what in the development and implementation of regional policy; strengthen the Concept of Regional Policy, to more clearly specify the broad targets of the Government's regional policy and the particular aspects of the central government's role; develop administrative structures over time, but don't tie regional development entirely to these structures; address issues related to disparities in basic services through equalization transfers, and safety nets; and, strengthen the financial accountability, and after this, the ability of regions to raise revenues. Furthermore, a transparent system of allocation for a public investment that focuses on key national infrastructure, should be created, and efforts to improve the investment climate overall, as opposed to pursuing investment enclaves should be supported, while policies that help develop small and medium enterprises should be further pursued.